Alternatif Pengembangan Pendidikan Berdasarkan “Nilai” Kebutuhan Khusus - Lake, Silverius CJM (Bina Nusantara University, 2015)
The Community College is a kind of higher education. It focuses on diploma degree (the Two Year College). The objectives of Community College are to educate and to train students for getting working skills for jobs. The Community College has competencies that are suitable with the working area and the local needs. To run the Community College goodly and truly, values is needed. Those values influence the mission of Community College. The question was why Indonesian Higher Education accepts the Community College as a model of higher education. The problem was related to some models of higher education that do not fulfill the demands of companies yet. Therefore the Community College becomes a choice to answer the demands of industries and etrepreneurship. The right references to learn about Community College are American Community Colleges such as Highline Community College (Seattle, WA) and Kapi’olani Community Collere (Honolulu, HI). Each of those Community Colleges has the best program for example Highline Community College in Business Management, then Kapi’olani Community College in Culinary Arts. This article used descriptive and argumentative method to show the importance of Commuity College in Indonesia.